SPEECH ACT EXPRESSIONS IN THE ADVERTISEMENTS ON TELEVISION : A CASE STUDY OF EIGHT ADVERTIMEMENTS BOTH COSMETICS AND CELL-PHONE PROVIDERS - Dini Hajar Marpuah, - (2009)
ABSTRACT The study entitled "Speech Act expressions in the Advertisements on Television" seeks to illuminate the types of speech acts based on Searle (1979) and the approaches of advertisements proposed by Book and Schick (1996). This study uses a qualitative method to analyze the collected data in this research. The data sources are in the form of verbal texts, namely, statements of the speaker's dialogue and narration both cosmetic and cell-phone provider advertisements. This advertisements were taken from several private TV stations presented during 1st August - 31st December 2008. The eight advertisements were chosen and categorized into four styles, namely, dramatizations, demonstrations, presentations, and testimonials. These commercials were classified into three tones, namely, factual, emotional, and humorous. Furthermore, the research was conducted to investigate the types of speech acts expressed in these different styles and tones of advertisements, namely, representatives, directives, commissives, expressives, and declaratives. The research presented 10 commissives and 10 representatives of all 31 statements that show speech act expressions. In addition, these two types respectively show a dominant number up to 32.26 %. Declaratives are appeared with the percentage 16.13 %. Both directive and expressive rates are 9.67 %. This research is expected to develop linguistic concept and knowledge for students who are interested in learning speech acts expressions in several utterances, especially in advertisements.